How to communicate smartly with your house?. (19th May 2011) - Rouillard, Jose; Tarby, Jean-Claude
We are involved in conceiving and implementing man?machine interfaces allowing multimodal and situated dialogue in order to interact with smart digital environments. Several methods are presented depending on how and what the user can say. We describe our approach and some tracks to permit to end-users to communicate more naturally with their house, by speech or by gesture, for instance. Some applications based on workflow description are presented to show how designers are able to model their own man?machine dialogue. Finally, this work is complemented with a Model Driven Engineering approach using Statecharts for a smart digital home.